Упростите выражение:1) sina/(1+cosa)2) (1+cos4a)/sin4a3) tg2a/(tg4a-tg2a)Прошу подробно, с выполнением каждого действия и пояснением формулой.

Упростите выражение: 1) sina/(1+cosa) 2) (1+cos4a)/sin4a 3) tg2a/(tg4a-tg2a) Прошу подробно, с выполнением каждого действия и пояснением формулой.
Гость
Ответ(ы) на вопрос:
Гость
1) sina/1-cosa = sina/ 2sin^2(a/2)=sin(a/2*2)/2sin^2(a/2)=... a/2=b ...=sin2b/2sin^2b= 2sinbcosb/2sin^2b=cosb/sinb = ctgb=ctg(a/2)
Не нашли ответ?
Ответить на вопрос
Похожие вопросы